2018
DOI: 10.1093/neuros/nyy023
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical Approach to the Anterior Nucleus of Thalamus in Patients With Refractory Epilepsy: Experience from the International Multicenter Registry (MORE)

Abstract: The results of this registry support the use of TV lead trajectories for ANT-DBS as they have a higher probability in placing contacts at ANT-TR, without appearing to compromise procedural safety. Follow-up data collection is continuing in the MORE registry. These data will provide outcomes associated with TV and EV trajectories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 16 publications
2
60
0
2
Order By: Relevance
“…This electrode was implanted using an extraventricular approach and was placed posterolaterally to the target at the border between the ventral lateral nucleus and the ANT instead of in the ANT proper. In a study of patients who underwent ANT DBS for refractory epilepsy, Lehtimäki et al found that 29.5% of the extraventricular approach DBS placements and 10.3% of the transventricular approach DBS placements were off target. This highlights a relatively common complication of ANT placement of which providers should be aware and illustrates that postoperative imaging is essential in confirming accurate surgical placement.…”
Section: Discussionmentioning
confidence: 99%
“…This electrode was implanted using an extraventricular approach and was placed posterolaterally to the target at the border between the ventral lateral nucleus and the ANT instead of in the ANT proper. In a study of patients who underwent ANT DBS for refractory epilepsy, Lehtimäki et al found that 29.5% of the extraventricular approach DBS placements and 10.3% of the transventricular approach DBS placements were off target. This highlights a relatively common complication of ANT placement of which providers should be aware and illustrates that postoperative imaging is essential in confirming accurate surgical placement.…”
Section: Discussionmentioning
confidence: 99%
“…18,44 One potential cause for outcome variation is inadequate DBS targeting: for instance, approximately 10% of electrodes were not within the ANT in the SANTE trial and the Medtronic Registry for Epilepsy (MORE) study. 30,50 Suggested improvements in direct ANT targeting have been proposed; 10,40 however, insufficiencies in direct structural targeting in DBS have been previously illustrated. 36,37 In this pilot study, we aimed to assess potential differences in resting-state functional connectivity profiles from volumes of tissue activated (VTAs) after ANT DBS in responders and nonresponders.…”
mentioning
confidence: 99%
“…The Oslo study used an extraventricular approach, which may make it even more difficult to hit the central part of ANT. A consensus report based on an international multicenter registry have recently concluded that direct targeting and a transventricular approach should be preferred for DBS implantations to the ANT . The success rate when placing at least one contact at the ANT target region bilaterally was 84% with a transventricular route, compared to 58% with an extraventricular route …”
Section: Discussionmentioning
confidence: 99%
“…Later studies have discussed the importance of a correct implantation site and advocated that direct MRI visualization of the desired target is essential for a favorable outcome in ANT‐DBS . ANT target identification in the Oslo patients was performed in the same way as in the SANTE study, using the same coordinates that were described in the pilot studies listed in the original SANTE article, and that were confirmed through personal communication with the SANTE authors.…”
Section: Introductionmentioning
confidence: 97%